The Effect of Socioeconomy on Chronic Energy Deficiency among Pregnant Women in the Sudiang Raya Health Center, 2019 - Purwanto, Nofita Setiorini Futri; Masni, Masni; Bustan, M. Nadjib (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Chronic energy deficiency (CED) is a condition of malnutrition of pregnant women which have an advanced impact in the form of health problems and complications in the mother and baby. For this reason, it is necessary to work toward prevention by knowing the socioeconomic influence on CED. AIM: The aim of the study was to determine the effect of socioeconomics on the incidence of CED in pregnant women. METHODS: This research is observational analytic with case–control research design. A sample of 99 pregnant women was taken from the working area of the Sudiang Raya Health Center. This sample consisted of 33 case groups of mothers with CED and 66 control groups of pregnant women who did not suffer from CED who had met the inclusion and exclusion criteria of the study. Data were analyzed using analysis Chi-square and multiple logistic regression. RESULTS: The results showed that maternal occupation (p = 0.018; odds ratio [OR] = 6.091; confidence interval [CI] 95% 1.367–27.133) was significant for CED, whereas that education (p = 0.213; OR = 0.593; CI 95% 0.260–1.351) and income (p = 0.576; OR = 0.733; 95% CI 0.247–2.179) are not significant to CED. Based on multivariate analysis we found that the most influential factor was occupation (adjusted OR = 11.734, CI 95% 1.253–109.91). CONCLUSION: Based on the results of research and discussion, it can be concluded that work affects the CED in pregnant women, while maternal education and income have no effect on CED in pregnant women. Occupation is the most influential factor on the CED, women who do not work have a risk of 11.734 times experiencing CED compared to women who work.